Infectious Diseases Clinician's Variation in the Management of Pediatric Staphylococcus aureus Bacteraemia and Equipoise for Clinical Trials - Anita J. Campbell; Anita J. Campbell; Anita J. Campbell; Steven Y. C. Tong; Steven Y. C. Tong; Joshua S. Davis; Joshua S. Davis; Alasdair P. S. Munro; Christopher C. Blyth; Christopher C. Blyth; Christopher C. Blyth; Christopher C. Blyth; et al. (Frontiers Media S.A., 2019)
Background: Pediatric Staphylococcus aureus bacteraemia is one of the leading causes of community-acquired blood-stream infection in the developed world; however, our understanding of management practices by treating clinicians is limited.Methods: The authors designed a web-based clinician survey with support from the Australian and New Zealand Pediatric Infectious Diseases group, of the Australasian Society of Infectious Diseases. Clinicians were presented with three pediatric cases of varying severity. Antibiotic choice, durations of intravenous and oral therapy and research priorities for pediatric S. aureus bacteraemia trials were gauged.Results and Conclusion: Large variation in antibiotic prescribing amongst clinicians is demonstrated and increased, corresponding with escalating case complexity and persisting MRSA bacteraemia. Most clinicians chose defining optimal duration of therapy for S. aureus bacteraemia as their top clinical trial priority. These findings highlight the importance of prioritizing pediatric S. aureus bacteraemia clinical trials, to inform guidelines and best practice management.